Observations of Stably Stratified Flow through a Microscale Gap - Vassallo, Daniel; Krishnamurthy, Raghavendra; Menke, Robert; Fernando, Harindra J. S. (Journal of the atmospheric sciences, 2021)
This paper reports the findings of a comprehensive field investigation on flow through a mountain gap subject to a range of stably stratified environmental conditions. This study was embedded within the Perdigão field campaign, which was conducted in a region of parallel double-ridge topography with ridge-normal wind climatology. One of the ridges has a well-defined gap (col) at the top, and an array of in situ and remote sensors, including a novel triple Doppler lidar system, was deployed around it. The experimental design was mostly guided by previous numerical and theoretical studies conducted with an idealized configuration where a flow (with characteristic velocity U 0 and buoyancy frequency N ) approaches normal to a mountain of height h with a gap at its crest, for which the governing parameters are the dimensionless mountain height G = Nh / U 0 and various gap aspect ratios. Modified forms of G were proposed to account for real-world atmospheric variability, and the results are discussed in terms of a gap-averaged value G c . The nature of gap flow was highly dependent on G c , wherein a nearly neutral flow regime ( G c < 1), a transitional mountain wave regime [ G c ~ O (1)], and a gap-jetting regime [ G c > O (1)] were identified. The measurements were in broad agreement with previous numerical and theoretical studies on a single ridge with a gap or double-ridge topography, although details vary. This is the first-ever detailed field study reported on microscale [ O (100) m] gap flows, and it provides useful data and insights for future theoretical and numerical studies.